The belt and road initiative as a hybrid international public good - İbrahim Öztürk (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2019)
The Belt and Road Initiative (BRI) is a Chinese endeavor to create an international public good (IPG) for bringing a cooperative solution to existing infrastructure deficits, mainly in the Eurasian landmass. This article aims to question the institutional quality of the BRI as a global governance platform with IPG characteristics in emerging political and economic oligopolistic markets. The central hypothesis of the article is that in order to successfully address both the conflicting and the overlapping demand and supply conditions in the rising multiplex world, the BRI should blend the Western experience of IPG creation in the post-World War II era with that of China's recent development. Such an amalgamation would also support China's integration in the global system as well as complement its weaker aspects. This type of synthesis of diverse experiences would help the BRI to evolve as a new brand of "hybrid IPG." In terms of methodology, an institutional economic theory with an interdisciplinary approach is employed in addressing collective action problems and agency issues and, therefore, in offering a win-win game in infrastructure-oriented cooperation. We found that although the BRI has striking achievements in terms of quantitative criteria, because of qualitative issues concerning its institutional governance structure, not only is the emergence of several managerial-coordination problems unavoidable, but destructive geopolitical rivalries and conflicts would also be triggered. The article concludes that, first, by applying the principles of international "good governance," the BRI would become a fully rule-based multilateral initiative; and second, China needs to show through working modalities and measurable outcomes along the BRI how its systemic values would contribute to the provision of such a hybrid IPG.
Keywords: F02; H4; P48; 330; global governance; international public goods; infrastructure connectivity; sustainable development; Belt and Road Initiative; multiplex world; cooperation; agency issues